In-situ synthesis of silver nanoparticles on cellulose and its catalytic performance. Issue 9 (2nd September 2022) - Huang, Yingchun; Li, Jialing; Zhou, Lei; Cheng, Chen; Hu, Ziqiang; Peng, Zhiyuan
Abstract: The chlorinated hydroxyethyl cellulose (HEC-Cl) was prepared by the chlorinated reaction of hydroxyethyl cellulose (HEC) and thionyl chloride, and dopamine-modified hydroxyethyl cellulose (HEC-DA) was prepared by the reaction of dopamine and HEC-Cl. The nano-silver supported on dopamine-modified cellulose (HEC-DA@AgNPs) was obtained by immersing the HEC-DA in AgNO3 solutions, where silver ions are absorbed and reduced by catechol groups. The X-ray photoelectron spectroscopy spectra of HEC-DA@AgNPs shows that the silver nanoparticles was loaded in the HEC-DA, and the diameter of AgNPs on the surface of HEC-DA is about 20 ± 10 nm. The catalytic activity was detected by the reduction of 4-NP, and it could be accomplished within 3 min with an apparent rate constant of 22.9 × 10 −3 s −1 . Therefore, the HEC-DA@AgNPs is expected to be a promising catalytic material. GRAPHICAL ABSTRACT: UF0001